306 Exploring the palliative care input provided to those born with Edward's and Patau's syndrome in the belfast trust. (17th August 2022) - Moore, Rachel; Haddick, Anne; Kapur, Sarah
Abstract : Aims: Edward's syndrome (Trisomy 18) is rare and associated with a poor prognosis, however 13% of babies live beyond 1 year of life in the UK. The reported incidence of Edwards is 3/10, 000 births every year whilst Patau Syndrome (Trisomy 13) is 2/10, 000. The aim of this audit was to look at the incidence of both Patau's and Edward's syndrome in the Belfast trust over a ten year period and review documentation around antenatal care planning and postnatal advance care planning. Methods: This was a retrospective audit looking at all the cases of Edward's and Patau's Syndrome in the Belfast Trust over a 10 year period. Case notes and electronic care records were reviewed and parameters were identified including incidence, method of diagnosis, median survival, clinical features, birth weight and documented palliative care plan were looked at. Results: There was an average incidence of 1 in 2320 live births of Edward's syndrome in the Belfast trust over 10 years. Only 4 out of 20 of these babies were diagnosed antenatally via amniocentesis. Of those who died in first year of life, the median survival was 5 days (range 1-201). We realised that these children can survive beyond the first year with one child surviving until 2 years and 6 months and another still alive at 2 years old who underwent a gastrostomy and oesophagostomy for a tracheoesophageal fistula. 20% and 15% of infants were discharged home and to the hospice respectively. There was an average incidence of 1 in 9280 babies born with Patau's syndrome in the Belfast trust. Of the 5 babies born over 10 years with Trisomy 13 only one was diagnosed antenatally. There was a median survival of 2 days, with one patient still alive at 4 years. Of these babies with Edward's and Patau's, 66% had a clear Palliative Care plan documented. Conclusion: This audit demonstrates what we already know – that there is a poor prognosis for babies born with Edward's and Patau's Syndrome, however, we have demonstrated that there is a broad range of clinical features, surprising survival ages and an alarmingly low number of infants diagnosed with these syndromes antenatally. We have also highlighted the need for a clear documented care plan from the moment of diagnosis, either antenatally or postnatally, which counsels the parents appropriately, allows them to prepare for the birth of and to grieve for their infant however they see fit, all the while working along with NICU/labour ward staff to ensure that their infant is kept as comfortable as possible. This is an essential element of the palliative care process for these patients. In conclusion, we have demonstrated potential for further improvement in our unit and are working on implementing changes in the near future.